Ice Jam Flooding on the Missouri River Near Williston, North Dakota - Wuebben, James L.; Gagnon, John J. (1995)
This investigation focused on ice related flooding along the Missouri River, just below the confluence with the Yellowstone River near Williston, North Dakota. This area is at the upper end of Lake Sakakawea. With the closure of Garrison Dam in 1953, Lake Sakakawea began filling, reaching operational levels in 1965. Changes in the hydraulics, sedimentation and ice regime of the Missouri River caused by the impoundment have led to an increase in the potential for overbank flooding. This report describes the ice regime assessment that was conducted to characterize ice jam flooding, the development of a method to predict the potential for ice jam occurrence and severity, and potential flood mitigation measures.